Exchange Rate Volatility, Pricing to Market and Trade Smoothing - Faruqee, Hamid (IMF Working Papers; Working Paper ;, 1997)
This paper investigates the consequences of exchange rate volatility on the variability of export prices and quantities in the presence of market segmentation and pricing to market. Firms stabilize destination prices through systematic price discrimination, limiting the degree of exchange rate pass-through. Consequently, the variability of exchange rates is not fully translated into prices and quantities at the point of destination. Empirical estimates using aggregate price data for the G-7 industrial countries show incomplete pass-through in variances, with considerable variation among these countries. U.S. industry specific data also indicate incomplete pass-through in most cases, with considerable variation across industries.